Penanaman Nilai Akhlak Pada Anak Didik Dalam Pendidikan Islam - darmiah, darmiah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2023)
AbstractA perfect human being according to Islam is formed through consistent fostering of moral values. Moral values are taught and habituated to students by fostering, exploring, and shaping and directing students to form commendable moral actions, so that Islamic education can function as character education. The moral values instilled will become provisions for students in childhood and adulthood, so that the moral teachings instilled in students should be based on the Qur'an and as-Sunnah. This paper is a theoretical qualitative normative discourse, the primary sources in this article are normative texts such as Al-Quran, alhadith, and other juridical policies. The results of the discussion in this article conclude that Islam has methodological principles in instilling moral values in students, namely a) The principle of habituation. With habituation, a person can be istiqomah with what he does so that it can become a character for him which will provide great benefits in one day, later. b) The principle of exemplary. This principle will emerge a positive environment for students, because all the senses of students only see something positive since the nature of students in general is a good imitator. Therefore, families, educational institutions and social systems plays an important role in the exemplary system.Keywords: Morals, Students, Islamic Education  Manusia yang paripurna menurut Islam dibentuk melalui pembinaan nilai akhlak secara konsisten. Nilai-nilai akhlaq di ajarkan dan di biasakan kepada peserta didik dengan cara membina, menggali, dan membentuk serta mengarahkan kepada peserta didik agar terbentuk perbuatan akhlak terpuji, sehingga pendidikan Islam dapat berfungsi sebagai pendidikan karakter. Nilai akhlak yang ditanamkan akan menjadi bekal bagi anak didik di masa kanak-kanak maupun dewasa, sehingga ajaran akhlak yang ditanamkan kepada anak didik hendaknya berdasarkan al-Qur’an dan al-Sunnah. Tulisan ini merupakan diskurs normatif kualitatif teoritis, sumber primer dalam artikel ini adalah naskah normatif seperti al-qur’an, alhadits, dan kebijakan yuridis lainnya. Hasil pembahasan dalam artikel ini menyimpulkan bahwa Islam memiliki prinsip metodologi dalam menanamkan nilai akhlaq kepada peserta didik yaitu a) Prinsip pembiasaan, dengan pembiasaan, seseorang bisa istiqomah dengan apa yang ia lakukan sehingga bisa menjadi tabi’at bagi dirinya yang akan memberikan manfaat yang besar di suatu hari nanti. b) Prinsip keteladanan, dengan keteladanan akan muncul suatu lingkungan yang postif bagi peserta didik, karena seluruh inderawi peserta didik hanya melihat sesuatu yang positif, karena hakikat peserta didik pada umumnya adalah peniru yang baik, oleh sebab itu, keluarga, lembaga pendidikan dan sistem sosial sangat memaikan peran penting dalam sistem keteladanan.Kata Kunci : Akhlak, Anak Didik, Pendidikan Islam